(untitled) (Contemporary Journal of Social Science Review, 2025)
This study evaluates the effectiveness of community service programs in Pakistani universities, focusing on student engagement, skill development, and societal impact. The research aims to explore how such programs contribute to students’ personal growth, civic responsibility, and practical learning. A quantitative research design was adopted, and data were collected through a structured questionnaire. The sample consisted of 200 students selected from six universities in Lahore—three public and three private institutions. The findings indicate that community service programs have a positive impact on students’ sense of responsibility, teamwork, and problem-solving abilities. However, the effectiveness varied between public and private universities due to differences in program implementation and institutional support. The study recommends strengthening institutional frameworks, providing proper training, and integrating community service into academic curricula to enhance outcomes. These results are valuable for policymakers, university administrators, and educators in developing more impactful community engagement initiatives in higher education.